Whole exome-seq and RNA-seq data reveal unique neoantigen profiles in Kenyan breast cancer patients - Wagutu, G.; Gitau, J.; Mwangi, Kennedy; Murithi, M.; Melly, E.; Harris, A.R.; Sayed, S.; Ambs, S.; Makokha, F. (Frontiers Media, 2024)
Background: The immune response against tumors relies on distinguishing between self and non-self, the basis of cancer immunotherapy. Neoantigens from somatic mutations are central to many immunotherapeutic strategies and understanding their landscape in breast cancer is crucial for targeted interventions. We aimed to profile neoantigens in Kenyan breast cancer patients using genomic DNA and total RNA from paired tumor and adjacent non-cancerous tissue samples of 23 patients.